“Actividad física y calidad de vida en el desarrollo de habilidades y destrezas de los niños de séptimo grado de educación general básica de la Unidad Educativa Luis Fernando Ruíz” - Ramos Yugcha, Joselyn Vanessa (2022)
The present work degree deals with physical activity and quality of life, as key factors for the integral formation of children. Therefore, physical activity due to the new dynamics of people's lives has been decreasing greatly. The problem proposed for the research is How physical activity, skills, and abilities influence the quality of life of children. Thus, having as variables physical activity and quality of life. The goal of this research is to strengthen physical activity and quality of life, in order to develop abilities and skills through didactic guides for motor development in children in the seventh year of Basic Education at the "Luis Fernando Ruiz" school. The methodology is based on descriptive research with a qualitative approach using data collection techniques such as surveys, interviews, and observations. The proposal is called "Guide of physical motor activities for the integral formation of children", it expresses physical activities in school, family, and community environments, whose purpose is to strengthen the quality of life of children through physical activities, developing skills of the children of the school. The research carried out will greatly improve the quality of life of students to achieve real and comprehensive training.